Measuring the level of the youth informal economy in Lithuania in 2004-2020 - Mangirdas Morkunas (Economies, 2022)
This paper investigates the development of the youth informal economy in Lithuania in 2004-2020. Specific youth-tailored multiple indicators multiple causes (MIMIC) model has been derived in order to estimate the level of the youth informal economy. In total, 173 direct phone interviews with company managers were conducted in order to acquire information for the MIMIC model calibration. It was revealed that during the investigated period, the youth informal economy fluctuated between 38.7% and 46.1% and was significantly higher compared with the overall informal economy in Lithuania. Although showing a strong correlation level (0.742) the overall informal economy within the country and the youth informal economy show slightly different developmental paths, the latter being more prone to higher increases during a crisis period.
Keywords: 330; informal economy; Lithuania; MIMIC; youth